Management of Pediatric Nonalcoholic Fatty Liver Disease by Academic Hepatologists in Canada: A Nationwide Survey. Issue 4 (October 2017) - Mouzaki, Marialena; Ling, Simon C.; Schreiber, Richard A.; Kamath, Binita M.
ABSTRACT: Background: The literature on the optimal clinical management of pediatric patients with nonalcoholic fatty liver disease (NAFLD) is limited. The objective of this study was to identify discrepancies in the care provided to patients with NAFLD by hepatologists practicing in academic centers across Canada. Methods: A nationwide survey was distributed electronically to all pediatric hepatologists practicing in university-affiliated hospitals using the infrastructure of the Canadian Pediatric Hepatology Research Group. The responses were anonymous. Results: The response rate to the survey was 79%. Everyone reported diagnosing NAFLD based on a combination of elevated transaminases and imaging suggestive of steatosis in the context of an otherwise negative workup for other liver diseases. Only 14% use liver biopsy to confirm the diagnosis. There are significant discrepancies in the frequency of screening for other comorbidities (eg, hypertension, sleep apnea, etc) and in the frequency of laboratory investigations (eg, lipid profile, transaminases, international normalized ratio, etc). Frequency of outpatient clinic follow-up varies significantly. Treatment is consistently based on lifestyle modifications; however, reported patient outcomes in terms of body mass index improvements are poor. Conclusions: There are significant discrepancies in the care provided to children with NAFLD by hepatologists practicing in academic centers across Canada. Abstract : Supplemental Digital Content is available in the text